Agricultural Research in the Sahel : Challenge and Response - Weijenberg, Jan (World Bank, Washington, DC, 2012)
The problem which this report seeks to address is the slow rate of technology generation of the agricultural research system in the Sahel. To overcome this problem, the report proposes to strengthen the national agricultural research systems in the region through a three-pronged effort: (a) institutional reforms of the national agricultural research systems to evolve an enabling environment for creativity, innovation and improved performance; (b) new modes of regional cooperation based on the principles of comparative advantage and the relative strengths of national agricultural research systems; and (c) a series of cross-cutting actions to support the revitalized national and regional efforts. It is expected that a more demand-driven national/regional research agenda and more vibrant linkages between scientists and clients will lead to faster rates of technology generation, as was demonstrated by the success of cotton research in the Sahel.